A Fast and Highly Selective Nitrite Sensor Based on Interdigital Electrodes Modified With Nanogold Film and Chrome-Black T - Luo, Haoyue; Lin, Xiaogang; Peng, Zhijia; Zhou, Yong; Xu, Shibin; Song, Ming; Jin, Lifeng; Zheng, Xiaodong (Frontiers in Chemistry, 2020)
Nitrite is a toxic substance, when excessive nitrite enters the human body, it will be seriously harmful to human. At present, the detection methods of nitrite are complicated to operate and require expensive detection instruments. Therefore, an effective, fast and highly selective nanogold film interdigital electrode sensors that can detect nitrite easily and quickly is developed in the work. Firstly, the variation of the sensitivity of nanogold film nitrite sensors with concentrations (1 mol/L, 10-1 mol/L, 10-2 mol/L, 10-3 mol/ L, 10-4 mol/L, 10-5 mol/L) was measured by experiments. Then, Chrome-black T was modified to the surface of the nanogold film interdigital electrodes by electrochemical polymerization, and the film of chrome-black T had affinity for nitrite ions, so nitrite ions were enriched on the sensor surface. The change law of the impedance signal of the modified nanogold film nitrite sensors after being added to different concentrations of sodium nitrite solution were also concluded. The study demonstrates that the larger the concentration of sodium nitrite solution is added to the modified interdigital electrodes, the smaller impedance and resistance of the modified interdigital electrodes are reflected. Finally, specificity of the modified interdigital electrode sensors has been demonstrated. The novel interdigital electrode sensors can detect the concentration of nitrite solution conveniently and quickly with only 30 s. Therefore, the prospect of applying the novel nanogold film interdigital electrode sensors to the detection of nitrite in blood, body fluid, food and drinking water is promising.